2019
DOI: 10.1001/jamaoto.2019.1765
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of 3- vs 2-Dimensional Endoscopy Using Eye Tracking and Assessment of Cognitive Load Among Surgeons Performing Endoscopic Ear Surgery

Abstract: IMPORTANCE Endoscopic ear surgery (EES) is an emerging technique to treat middle ear diseases; however, the interventions are performed in 2-dimensional (2D) endoscopic views, which do not provide depth perception. Recent technical developments now allow the application of 3-dimensional (3D) endoscopy in EES. OBJECTIVE To investigate the usability, advantages, and disadvantages of 3D vs 2D endoscopy in EES under standardized conditions. DESIGN, SETTING, AND PARTICIPANTS This cohort study conducted at a tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 16 publications
(28 citation statements)
references
References 42 publications
2
25
0
1
Order By: Relevance
“…Indeed, traditional 2D and modern 3D endoscopic techniques have recently been compared for surgeons performing endoscopic ear surgery. 9,19 Here, 3D endoscopy was shown to be suitable for endoscopic ear surgery and to have advantages, especially for less experienced surgeons. Taken together, the advantages of the endoscopic view and dissection of the middle ear appear to be superior to the microscopic technique (theme A5).…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, traditional 2D and modern 3D endoscopic techniques have recently been compared for surgeons performing endoscopic ear surgery. 9,19 Here, 3D endoscopy was shown to be suitable for endoscopic ear surgery and to have advantages, especially for less experienced surgeons. Taken together, the advantages of the endoscopic view and dissection of the middle ear appear to be superior to the microscopic technique (theme A5).…”
Section: Discussionmentioning
confidence: 99%
“…Unlike microscopically-trained surgeons, the mental model of endoscopic native surgeons is not yet consolidated. Similar to the literature regarding 3D endoscopy [ 15 ] the implementation of a relatively new technique by young surgeons may be facilitated by the more flexible mental representation of the technique. In contrast, microscopically experienced surgeons have to transform their fixed two-handed stereoscopic mental model into a one-handed two-dimensional model.…”
Section: Discussionmentioning
confidence: 99%
“…Many surgeons including the 2 authors have found the use of 3D endoscopy very helpful and there is evidence from other specialties that this is associated with a shorter learning curve and better depth perception. 11 At present, all 3D endoscopes require a 10 mm port against a 5 mm port for a high-definition 2D camera. We feel the extra 5 mm is a price worth paying but this needs to be evaluated by each surgeon to compare the pros against the cons (Table 1).…”
Section: Choose An Endoscope (Think Win–win)mentioning
confidence: 99%